Parental Absence Accompanies Worse Academic Achievements: Evidence Based upon a Sample of Left-Behind Children in Rural China - Fu, Mingchen; Bo, Wenjin Vikki; Xue, Yan; Yuan, Ti-Fei (Frontiers in Education, 2017)
In China, with the rapid urbanization and large amount of labor force migrating from rural to urban areas, an enormous number of children living in rural China are in the absence of parental care. The objective of the study was to investigate the academic performance of left-behind children under various statuses of parental absence. We investigated 3076 children (1761 non-left-behind and 1315 left-behind) regarding their academic achievement in different subjects. We found that children with different status of parental absence would perform differently on Chinese, mathematics, and English learning. In addition, left-behind children would be significantly more likely to get low scores in academic examinations as compared with non-left-behind children. Strengths and limitations of the study are discussed.